The History of Islam: New Directions (American Journal of Islam and Society, 1989)
History is very important from the ideological and educational standpointin addition to its importance as a discipline of knowledge and as information.The Qur’an teaches us, “Indeed in the stories of these men, there is a lessonfor those who can think.” [12:111] Educationally, then, for the new generationsand ideologically for those who are committed to Islam as a way of life,it is very important to get the message of history which enlightens us in dealingwith contemporary circumstances.Some introductory remarksIs it more correct to say Islamic history or Muslim history?Each description has its pros and cons. When you say “Islamichistory“ you care more about commitment to Islam andassessment accoding to Islamic criteria, since not everythtngwhich happened in the past or happens at present on theIslamic scene can really be considered Islamic. Historicalevents should be evaluated under such a term according toIslam whether they are social, cultural, political or economic.What may be positive in terms of a historical developmentor very important as a mere material accomplishment mayor may not be something important from the viewpoint ofIslam. Suppose that we have a very magnificent tomb madeby Muslims, would you consider this Islamic or not?Calling our history “Muslim history“ may draw a line betweenhuman behavior and Islam itself. History represents theoutcome of Muslim practices and each can be evaluatedamrdmg to Islam. It is just a development of Muslim thinkingand behavior- Muslim interaction with other human universaleffects. Muslim history is the product of Muslims as human ...